Beyond Mars and Venus: The role of gender essentialism in support for gender inequality and backlash. - Lea Skewes; Cordelia Fine; Nick Haslam (PLoS ONE, 2018)
It has been argued that gender essentialism impedes progress towards greater gender equality. Here we present a new gender essentialism scale (GES), and validate it in two large nationally representative samples from Denmark and Australia. In both samples the GES was highly reliable and predicted lack of support for sex-role egalitarianism and support for gender discrimination, as well as perceived fairness of gender-based treatment in the Australian sample, independently of two established predictors (i.e., social dominance orientation and conservative political orientation). In addition, gender essentialism assessed by the GES moderated some manifestations of the backlash effect: high essentialists were more likely to respond negatively towards a power-seeking female political candidate relative to a male candidate. Given the implications for possible workplace interventions, further work could usefully explore whether gender essentialism moderates other well-established forms of gender bias.